Perancangan Modul Verifikasi dan Metode Pemeriksaan Peralatan Produksi Sigaret Kretek Tangan di PT âXâ - Ongke, Deisy; Palit, Herry Christian (Jurnal Titra, 2013)
PT âXâ is one of the hand-rolled manufacturers cigarettes which using manual process to produce the cigarettes. There were no standardization for verify the production tools. So that every operators could verify those tools in different manners and in fact it caused problems in the production floor. Therefore, a standardization procedures, which is align with the company specification, is an obligatory. As the result of this work, we designed 21 modules for all brands manufactured by PT âXâ. Moreover, the study successfully establishes standard procedure, verification form, and verification report which can help maintenance operator to perform production tools verification in every locations.